2019
DOI: 10.5430/ijfr.v10n5p40
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Esteem and Influence of Friends via Social Media on Body Image Amongst Children

Abstract: Introduction: With the rise and fall of many communication platforms embedded into our everyday lives and the on-going maturity of the digitalization era, social media usage has tremendously increased over the past decade. The purpose of this research is to identify to what extent self-esteem and the influence of friends’ impact children's perception of their body image through social media and how powerful social media in influencing the body image of children.Methodology: The theoretical implication of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 113 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…Keberlanjutan, di sisi lain, menunjukkan pemeliharaan kemajuan dalam tingkat optimal yang dapat dicapai. Secara umum, istilah "perkembangan" mencakup proses pertumbuhan, penyesuaian, dan transformasi sepanjang kehidupan, meliputi dimensi fisik, kepribadian, sosio-emosional, kognitif, dan bahasa (Ahmad, 2019;Koniakou, 2022;Reisdorfer, 2023;Sattler, 2021). Ketika diterapkan pada anak-anak, perkembangan merujuk pada proses bertahap pembentukan karakteristik dan sifat yang dipengaruhi secara biologis ketika mereka belajar melalui pengalaman (Handayani & Maharani, 2022).…”
Section: Pendahuluanunclassified
“…Keberlanjutan, di sisi lain, menunjukkan pemeliharaan kemajuan dalam tingkat optimal yang dapat dicapai. Secara umum, istilah "perkembangan" mencakup proses pertumbuhan, penyesuaian, dan transformasi sepanjang kehidupan, meliputi dimensi fisik, kepribadian, sosio-emosional, kognitif, dan bahasa (Ahmad, 2019;Koniakou, 2022;Reisdorfer, 2023;Sattler, 2021). Ketika diterapkan pada anak-anak, perkembangan merujuk pada proses bertahap pembentukan karakteristik dan sifat yang dipengaruhi secara biologis ketika mereka belajar melalui pengalaman (Handayani & Maharani, 2022).…”
Section: Pendahuluanunclassified
“…While it is unfair to overgeneralize social media as a toxic medium to prevent a healthy body image, studies have proven that social media too, plays an impactful role in distorting a person's expectation in appreciating their own body. Posting an image on social media for "likes'' could boost a person's perception of body image but seeing others' selfies that might get more "likes" than your own, might cause disappointment and negative perception of body image (Ahmad, Idris, & Jing, 2019;Chua & Chang, 2016;Grogan, 2016;Tiidenberg, 2014). Holland and Tiggemann (2016) reported that those who engaged more in self-photo related activities on social media scored higher levels of bodyrelated and eating concerns.…”
Section: Social Media Body Image and Youthmentioning
confidence: 99%
“…However, studies examining the relationships between these two variables along with the variable of social media use seem to be limited. [ 18 , 19 ] This study aimed to investigate the relationship between self-esteem and social media use in adolescents and the mediating role of body image in this relationship. The literature review that was conducted for this study revealed no previous study examining the mediating role of body image in the relationship between social media addiction and self-esteem levels.…”
Section: Introductionmentioning
confidence: 99%